Where Microsurgical Tubal Reanastomosis Stands in the In vitro Fertilization Era - Hwa Sook Moon; Bo Sun Joo; Sang Gap Kim; Kyung Il Nam; Ja Seong Koo (Gynecology and Minimally Invasive Therapy, 2024)
Among various options of contraception, bilateral tubal ligation (BTL) remains the most frequently used method for women worldwide even at present. However, up to 30% of those who undergo BTL eventually change their minds and wish to conceive again for a variety of reasons, such as a change in marital status or simply wanting more children. In this case, we can either approach it surgically with tubal re-anastomosis (TA) or by in vitro fertilization (IVF)-embryo transfer. Despite the many advantages of TA which lead the American Society of Reproductive Medicine Committee Opinion to recommend it as the primary choice of treatment in posttubal ligation infertility in 2012, IVF is widely being chosen as the first-line treatment nowadays. This study will review the efficacy of TA in various aspects, including pregnancy rate, cost-effectiveness, feasibility, and accessibility, based on review of the literature and our experience. Through this study, we intend to provide a basis for gynecologists to consider TA as the first option in women who wish to conceive again after BTL in this day and age of IVF.